Community richness of amphibian skin bacteria correlates with bioclimate at the global scale - Kueneman, Jordan G.; Bletz, Molly C.; McKenzie, Valerie J.; Becker, C. Guilherme; Joseph, Maxwell B.; Abarca, Juan G.; Archer, Holly; Arellano, Ana Lisette; Bataille, Arnaud; Becker, Matthew; Belden, Lisa K.; Crottini, Angelica; et al. (Springer Nature, 2019)
Animal-associated microbiomes are integral to host health, yet key biotic and abiotic factors that shape host-associated microbial communities at the global scale remain poorly understood. We investigated global patterns in amphibian skin bacterial communities, incorporating samples from 2,349 individuals representing 205 amphibian species across a broad biogeographic range. We analysed how biotic and abiotic factors correlate with skin microbial communities using multiple statistical approaches. Global amphibian skin bacterial richness was consistently correlated with temperature-associated factors. We found more diverse skin microbiomes in environments with colder winters and less stable thermal conditions compared with environments with warm winters and less annual temperature variation. We used bioinformatically predicted bacterial growth rates, dormancy genes and antibiotic synthesis genes, as well as inferred bacterial thermal growth optima to propose mechanistic hypotheses that may explain the observed patterns. We conclude that temporal and spatial characteristics of the host’s macro-environment mediate microbial diversity.